Bloodstream infection caused by Bacteroides caccae in a patient with renal hypertension: a case report. Issue 10 (October 2021) - Yang, Yang; Zhang, Qingfang; Hu, Haitao; Zhang, Wenyun; Lu, Taohong
Bacteroides caccae is an anaerobic bacterium with a reportedly high isolation rate; however, it rarely causes bloodstream infections. Patients with hypertension are at increased risk of developing anaerobic bacterial infection. In this study, we report a case of bacteremia caused by B. caccae in a patient with renal hypertension and gastrointestinal hemorrhage. This study describes the clinical manifestations of bloodstream infection involving B. caccae to provide guidance for laboratory technicians and clinicians. A 42-year-old Chinese man was admitted for gastrointestinal hemorrhage and subsequently diagnosed with anaerobic blood infection. The pathogenic bacteria isolated from anaerobic blood culture bottles were identified as B. caccae by using an automatic bacterial identification instrument and mass spectrometry (MS). B. caccae is an intestinal opportunistic pathogen that can invade the intestinal mucosa and cause anaerobic bloodstream infection. Two or more sets of blood cultures and MS identification can greatly improve the positive detection rate of blood cultures of anaerobic bacteria. Furthermore, the increased drug resistance of anaerobic bacteria necessitates drug sensitivity tests for anaerobic bacteria in many hospitals. Thus, the early prevention and control of primary diseases with appropriate diagnoses and timely anti-infection therapies are necessary to reduce B. caccae bloodstream infection.